Gambaran Kesadaran dan Pengetahuan Masyarakat terhadap Tuberkulosis Paru - USWATUN, siti; Siti Munawaroh; Dian Nurhidayah (Ilin Institute, 2025)
Disease eradication programs that focus on efforts to prevent disease outbreaks, reduce morbidity and mortality rates, and reduce the negative consequences of communicable and non-communicable diseases. Tuberculosis (TB) is a world health problem, especially in Indonesia. One of the problems that is known to still be an obstacle in suppressing the spread of TB disease is a lack of understanding from the public, there are still many people who lack information and therefore have wrong perceptions regarding pulmonary TB disease. This service activity is carried out using the method of educating people about pulmonary TB to people who visit the health center, accompanied by the distribution of brochures and a questionnaire to each visitor to the health center. Understanding pulmonary TB disease will have a big impact on improving recovery and reducing the rate of transmission of pulmonary TB disease. Regular socialization accompanied by other socialization media, such as leaflets, will increase public understanding, so that more people will be aware of pulmonary TB disease.